Analisis Pengaruh Inflasi, Suku Bunga dan Indeks Produksi Industri terhadap Pertumbuhan Ekonomi Indonesia Pascapandemi (2018-2025) - Nugroho, Farhan; Alkena Sae Hafizah; Adzra Andriana; Anggun Mustika Anggraeni; Alfian Fadillah; Ahmad Setiawan Nuraya (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze changes in Indonesia’s economic cycle patterns in the post-pandemic period, as reflected in inflation, interest rates, and the industrial production index over the 2018–2025 period. The study adopts a quantitative approach employing a multiple linear regression model. The data utilized consist of secondary time-series data obtained from Bank Indonesia and the Central Statistics Agency (Badan Pusat Statistik). The empirical results indicate that, simultaneously, the explanatory variables exert a statistically significant effect on economic growth. Partially, interest rates and the industrial production index demonstrate a positive and statistically significant influence. In contrast, inflation does not exhibit a statistically significant effect at the 10% significance level. The coefficient of determination (R-Squared) of 0.9327 suggests that the model possesses substantial explanatory power in accounting for variations in Indonesia’s economic growth. The descriptive analysis indicates that Indonesia’s economy experienced a contraction of -2,07% in 2020 due to the COVID-19 pandemic, followed by a gradual recovery throughout the 2021–2025 period. These findings imply that post-pandemic shifts in Indonesia’s economic cycle patterns are more prominently driven by interest rate policy measures and real sector recovery relative to the role of inflation.